O tempo inteiro eu tenho que estudar: a relação entre ensino de história, juventude e música urbana no ensino médio - Silva Junior, Antonio Manuel da (2016)
This study aims to examine the possibility of relations between the songs of urban music with youth and History Teaching. At another point the study will seek in the school culture and high school tools that relationship with textbooks and evidence ENEM. Used as a source for our research volume 3 of three collections of textbooks of history aimed at high school and the 1998 ENEM of evidence to 2015. By analyzing the textbooks, we conducted a general approach of the book and the use of music the main text of books or in their activities. Regarding the evidence ENEM, we seek to observe what the main themes discussed the issues and analysis from the ESMS Reference Matrix matters containing songs. This research also laid up on an analysis of the importance of secondary education for youth, their relationship with the content and curriculum and the importance of the formulation of historical knowledge, the school knowledges and historical consciousness. This study is linked to the line of research "Teaching of History and Historical Knowledge" Program Graduate of the Federal University of Paraiba, with specialization in "History and Historical Culture." Through it, we seek to trace the main links between the rock and the youth; youth and high school; school Culture and History Education; the songs and secondary education tools (Textbooks and ESMS) observing the progress in education of high school in Brazil. It is also the focus of this study the analysis of the song as a historical document and how to treat / work with it.